OPTIMIZING PROJECT-BASED TRY ACTIVITY TO IMPROVE THE DIMENSION OF STUDENTS’ COGNITIVE PROCESS - I Wayan Widiana; I Made Suarjana (Universitas Negeri Yogyakarta, 2019)
This study was aimed at determining the differences in the dimensions of cognitive processes between groups of students who are taught with project-based trying learning activities and groups of students who are taught with conventional learning activities. This research is a quasi-experimental study with a post-test only control group design. The population of this study was the fifth-grade students of the 2016/2017 academic year in the Curriculum 2013 Elementary School in Buleleng Regency, which amounted to 326 students. The samples were taken by cluster random sampling which amounted to 60 students. The data collected in this study were the results of the dimensions of cognitive processes by using 20 multiple-choice tests and 5 item essays on the ecosystem theme. The hypothesis was tested using inferential t-test statistics. The results show that there are significant differences in the dimensions of cognitive processes between groups of students who were taught with project-based trying activities and groups of students who were taught using conventional learning activities. The optimizing project-based trying activities has a positive effect on the dimensions of students' cognitive processes.PENGOPTIMALAN AKTIVITAS MENCOBA DENGAN BERBASIS PROYEK UNTUK MENINGKATKAN DIMENSI PROSES KOGNITIF SISWAPenelitian ini bertujuan untuk mengetahui perbedaan dimensi proses kognitif antara kelompok siswa yang dibelajarkan dengan aktivitas pembelajaran mencoba berbasis proyek dan kelompok siswa yang dibelajarkan dengan aktivitas pembelajaran konvensional. Penelitian ini merupakan penelitian quasi eksperimen dengan rancangan penelitian post test only control group design. Populasi dari penelitian ini adalah siswa kelas V Tahun Pelajaran 2016/2017 di SD rintisan Kurikulum 2013 Kabupaten Buleleng yang berjumlah 326 orang. Sampel diambil dengan cara cluster?random sampling yang berjumlah 60 orang. Data yang dikumpulkan dalam penelitian ini adalah hasil dimensi proses kognitif dengan menggunakan tes pilihan ganda sebanyak 20 butir dan esai 5 butir soal pada tema ekosistem. Hipotesis diuji dengan menggunakan statistik inferensial t-test. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan pada dimensi proses kognitif antara kelompok siswa yang dibelajarkan dengan aktivitas pembelajaran mencoba berbasis proyek dan kelompok siswa yang dibelajarkan dengan aktivitas pembelajaran konvensional Pengoptimalan aktivitas mencoba berbasis proyek berpengaruh positif terhadap dimensi proses kognitif siswa.